„Capitalistic Exploiter“ František Křižík in Marxistic Historiography and Journalism (Theatrum historiae, 2012)
František Křižík is one of the few technicians in the Czech history who is perceived as a national hero. This study deals with the notion of his personality as a “capitalistic entrepreneur” as interpreted by Marxistic society in the fifties of the 20th century.
Keywords: František Křižík; Křižík’s tradition; 1950s; Marxistic interpretation